Retelling Story through Picture Series to Improve Speaking Skill the Eleventh Grade Students of SMAN 6 Pangkep - Hardianti Hardianti; Syarifuddin Dollah; Geminastiti Sakkir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to (1) find out whether there is an improvement in the speaking skill of students through retelling stories using picture series and (2) find out whether there is an increase in speaking skill through using picture series on vocabulary, and pronunciation. The population of this research is the eleventh-grade students of SMAN 6 Pangkep given by the school. A speaking test was used as an instrument to collect data in this study. The research design used in this research is a pre-experimental, which is one group pretest-posttest design with the sample from class XI MIA, which consists of 19 students using cluster random sampling technique. The mean score of the post-test was 7.00 and which is classified as a very good score, while the standard deviation was .745. The researchers analyzed the data quantitatively by using inferential statistics SPSS 26. The results of the data analysis showed that using retelling story through picture series can improve students' speaking skill. It can be proven by the acquisition of significance value (2- tailed) was 0.000 less than 0.05. It means H0 is rejected and H1 is accepted. So, it can be concluded that the use of retelling story through picture series improves the speaking skill of the eleventh-grade students of SMAN 6 Pangkep.